Intra articular hyaluronic acid injection, is it a wastage of money or justified? - Jesalpura, Bhavesh H.; Gajjar, Sharvil H. (International Journal of Research in Orthopaedics, 2017)
Background: Osteoarthritis of knee (OA Knee) is one of the most common form of joint disease and affects everyone in different proportion with aging. To reduce the burden on society and improve the productive life various modalities of treatment are suggested. Our goal was to find out how much Intra Articular Hyaluronic acid injection (I/A HA inj.) is effective and safe. Methods: We have done a retrospective single blind study on 60 patients of OA Knee according to ACR Criteria, Grade I and II, who were treated with I/A HA inj. of a single brand. They were followed up up to 3 year after last injection and clinical assessment done based on VAS Scale and WOMAC Score. Results: Out of 60 patients who have been given I/A HA injection, patients below age of 50 and ACR Grade I OA Knee, responded well with injection. However patients above age of 50 and ACR Grade II OA Knee responded poorly and require some other form of treatment as early as 1 month after stopping injection. Conclusions: Though OA Knee is a degenerative disease which requires long term follow up to justify use of I/A HA injection, We believe that in early cases of OA Knee and Patients below age of 50 years, this treatment modality can work well and may prolong active life and delay surgical intervention and hence cost benefit ratio justifies use of this treatment modality.